ANALISIS PENGARUH KARAKTERISTIK KOMITE AUDIT DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hendi, Hendi; Lisniati, Septi (Global Financial Accounting Journal, 2020)
This research is conducted to determine the impact of audit committee characteristics and ownership structures on earnings management of companies listed on Indonesian Stock Exchange (IDX). This research used 324 companies listed on IDX in the period 2011-2015 as the sample. The results of this study indicate that institutional ownership, firm size, return on asset, and operating cash flow show the significant impact on earnings management in both positive and negative ways. On other hand, the results also indicate that the independence, diligence, and size of audit committee, foreign ownership, managerial ownership, governmental ownership, individual ownership, and leverage are not able to affect earnings management activity significantly.